1996
DOI: 10.2214/ajr.167.4.8819407
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhancement and quantitative signal analysis in MR imaging of multiple myeloma: assessment of focal and diffuse growth patterns in marrow correlated with biopsies and survival rates.

Abstract: MR imaging with opposed gradient-recalled echo sequences and contrast enhancement provided data that allowed us to classify infiltration patterns and to quantify diffuse marrow involvement in multiple myeloma, both of which correlated to clinical staging and biopsy. Also, the MR data was of prognostic value. Therefore, like laboratory parameters, biopsies, and radiographs, MR imaging can be a supporting pillar in staging and planning treatment of patients with multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
2
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 0 publications
1
96
2
5
Order By: Relevance
“…A diffusely abnormal pattern of bone marrow also correlated with more marked alterations in other clinical parameters of disease activity such as serum calcium, t32 microglobulin and hemoglobin levels, indicating more severe disease than found in patients with a focally abnormal MRI pattern of bone marrow [8]. Stabler et al [1] evaluated five types of infiltration patterns and confirmed the prognostic value of MRI in staging of, and in planning treatment for, multiple myeloma. They also reported a correlation between the pattern of infiltration and the degree of contrast enhancement: A greater than 40% increase in signal intensity compared with baseline after contrast administration correlated with diffuse tumor infiltration of marrow.…”
Section: Lymphoproliferative Diseasesmentioning
confidence: 92%
See 2 more Smart Citations
“…A diffusely abnormal pattern of bone marrow also correlated with more marked alterations in other clinical parameters of disease activity such as serum calcium, t32 microglobulin and hemoglobin levels, indicating more severe disease than found in patients with a focally abnormal MRI pattern of bone marrow [8]. Stabler et al [1] evaluated five types of infiltration patterns and confirmed the prognostic value of MRI in staging of, and in planning treatment for, multiple myeloma. They also reported a correlation between the pattern of infiltration and the degree of contrast enhancement: A greater than 40% increase in signal intensity compared with baseline after contrast administration correlated with diffuse tumor infiltration of marrow.…”
Section: Lymphoproliferative Diseasesmentioning
confidence: 92%
“…However, very early in the disease, tumor cells may not completely replace fat cells in marrow and thus the resultant marrow signals can be normal on T1-and T2-weighted spin echo (SE) images. In multiple myeloma, the amount of marrow fat can even increase initially because the tumor cells produce biochemical factors that inhibit hematopoiesis [1]. When more extensive, lymphoproliferative tumors in marrow are low in signal intensity on T1-weighted SE images and high in signal intensity on T2-weighted SE images.…”
Section: Lymphoproliferative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…22 According to literature, this pattern corresponds to an only low-grade diffuse infiltration of bone marrow intermingled with focal fat islets (with a hyperintense signal on T1-weighted images). 23 Generally low signal intensity of the bone marrow on T1-weighted images in combination with a general increased signal intensity on T2-weighted images were rated as diffuse infiltration pattern and subcategorized as "moderate" (hyperintense on T1-weighting compared to the intervertebral What's new? Plasma-cell disorders such as multiple myeloma (MM) and monoclonal gammopathy of undetermined significance (MGUS) may produce different cellular patterns in the bone marrow.…”
Section: Image Analysismentioning
confidence: 99%
“…Plasmacytomas can occur in various locations. Studies have shown that the MRI findings correlate with treatment response and survival (14).…”
Section: Plasmacytomamentioning
confidence: 99%